Prediction of a New Cascaded Hybrid Multilevel Inverter with Less Device Count - C.R. Balamurugan; S.P. Natarajan; R. Bensraj (Institute of Advanced Engineering and Science, 2016)
Multilevel inverters have been opted for high power applications due to reduced harmonic distortion, less device voltage stress and modular structure. This work proposes new modified hybrid H-bridge multilevel inverter using auxiliary switch. This proposed inverter produces five levels output with five power devices and clamping diodes as a phase voltage and nine levels as a line voltage.The levels of the inverters are decided based on the phase voltage not on the line voltage. In this paper the performance of the proposed inverter are measured in terms of line voltage. However, by increase in the number of levels the proposed inverter with reduced number of switches produces low switching losses and improves the efficiency of the inverter. This method achieves the variation of Total Harmonic Distortion (THD) in the inverter and output voltage is observed for various modulation indices. Simulation is performed using MATLAB-SIMULINK for line to line output voltage. Variable Amplitude Phase Disposition (VAPD) strategy provides output with relatively low distortion for all the strategies. It is also seen that VAPOD is found to perform better for all strategies since it provides relatively higher fundamental RMS output voltage.